PEMENUHAN ASPEK CARA PRODUKSI PANGAN OLAHAN YANG BAIK (CPPOB) PADA UMKM TAGANANG KOTA BALIKPAPAN - Vivie Sulastri; Miftakhur Rohmah; Maulida Rachmawati; Maghfirotin Marta Banin (Universitas Mataram, 2023)
Good Processed Food Production Method (GPPOB) is one of the important factors to meet the food safety standards that are produced and to ensure that the resulting products are of good quality and are safe. Food safety requirements are very important to be able to prevent food from physical, chemical and other biological contaminants that can disturb, harm and endanger public health. The purpose of the assistance is to increase empathy and concern for MSMEs in preparing the requirements and application of CPPOB to fulfill BPOM distribution permits for MSMEs in Taganang, Balikpapan City. The methods used are 1) Carrying out observations and interviews, which are techniques that are carried out directly on the object of research, namely CPPOB, 2) Providing assistance in implementing aspects of CPPOB, namely methods that can provide assistance and guide MSMEs in improving the implementation of CPPOB and 3) carry out monitoring and evaluation, namely knowing the final condition of MSMEs after implementing CPPOB. The results of the assistance to the Taganang MSMEs for the initial condition assessment found 14 aspects that had not been implemented, with a score of 70 or included in a C rating (Less), after the assistance was carried out to improve production facilities, an increase in the CPPOB aspect obtained a score of 111 included in rating B (Good ). This shows that Taganang MSMEs have fulfilled the requirements for implementing the CPPOB aspects. UMKM Taganang has shown good changes in the implementation of CPPOB aspects.